COMPARATIVE STUDY OF MAE, SONICATION& CONVENTIONAL METHODS IN EXTRACTION OF M. SPICATA (DALZ.) NICOLSON - D.G.KARPE,; S.P.LAWANDE, (International Journal of Pharma and Bio Sciences, 2016)
A conventional method of extraction requires high energy and more time. Soxhlet extraction is thermal extraction method. Microwave assisted extraction (MAE) and sonication methods are new techniques which requires less time and are more efficient than thermal extraction & maceration methods. Microwave is an electromagnetic radiation consists of electric and magnetic field having a frequency ranged from 0.3 to 300 GHZ, it penetrates into certain materials and interacts with polar components to generate heat, and hence selective targeted materials can be heated and extracted. Sonication is sound energy which agitates particles. Ultrasonic energy of 720 KHZ is used for extraction. A MAE and Sonication method gives better yield of extracts within smaller time. In MAE extractive value is better compared with other extraction methods. Moullava spicata aerial parts (powdered plant material) extracted in different solvents (Petroleum ether, Ethyl acetate, Methanol) and using different extraction techniques. Extractive value is determined and antibacterial & antifungal analysis was done. Crude extracts obtained from MAE shows better results. Another important application of MAE is that, it was carried out at low temperature hence the chance of decomposition of organic compounds is minimum as compared to thermal extraction.